Heart rate variability in children with type 1 diabetes mellitus - Gardim,Camila Balsamo (2014)
OBJECTIVE:To gather current information about the effects of type 1 diabetes mellitus on children's cardiac autonomic behavior.DATA SOURCES: The search of articles was conducted on PubMed, Ibecs, Medline, Cochrane, Lilacs, SciELO and PEDro databases using the MeSH terms: "autonomic nervous system", "diabetes mellitus", "child", "type 1 diabetes mellitus", "sympathetic nervous system" and "parasympathetic nervous system", and their respective versions in Portuguese (DeCS). Articles published from January 2003 to February 2013 that enrolled children with 9-12 years old with type 1 diabetes mellitus were included in the review.DATA SYNTHESIS: The electronic search resulted in four articles that approached the heart rate variability in children with type 1 diabetes mellitus, showing that, in general, these children present decreased global heart rate variability and vagal activity. The practice of physical activity promoted benefits for these individuals.CONCLUSIONS: Children with type 1 diabetes mellitus present changes on autonomic modulation, indicating the need for early attention to avoid future complications in this group.